Peningkatan Kemmapuan Membaca Pemahaman Dengan Model CIRC Berbantuan Media Buku Cerita Bergambar - Ilmiahwati, Tibta Ilmiahwati; Purnanto, Arif Wiyat Wiyat; Hajron, Kun Hisnan (Paedagogie, 2024)
The study aims to determine the effect of the Cooperative Integraed Reading and Composition(CIRC) model on improving students reading comprehension skills. This research is motivated by several prblems, including grade II student who have not comprehension. It can be seen that when students are asked questions about the content of the reading read, students cannot answer quickly and must reopen the reading material they read. When students are invited to rewrite the content of the reading text that has been read, students still do not understand so they have to reread the reading text. And the right learning model has not been applied to Indonesian language learning. The research used is classroom action research. In this classroom action research, peer observers directly observed learning activitiesusing the CIRC model in class. This tesearch wasconducted at SDIT Ar Risalah Secang, Secang Village, Secang District, Magelang Regency. The researcher chose SDIT Ar Risalah Secang because no one had conducted research at this school. The increase in learning outcomes can be seen from the percentage of student learning completeness from cycle I and cycle II. In the first cycle of the first meeting as many as 2 students with a percentage of 9.09% were declared complete and in the second meeting as many as 10 students with a percentage of 45.45% were declared complete. In the second cycle of the first meeting as many as 15 students with a percentage of 68.18% were declared complete and in the second meeting as many as 19 students with a percentage of 86.36% were declared complete. This can be evidence that the use of the CIRC model can improve the reading comprehension ability of grade II students of SDIT Ar Risalah Secang Keywords: CIRC model, reading comprehension ability,matery learning.